Immature stages of three species and new records of five species of Phylloicus Müller (Trichoptera, Calamoceratidae) in the northern region of Brazil - de Souza-Holanda, Paula Mayara; Pes, Ana Maria; Hamada, Neusa (Zootaxa, 2020)
The larvae, pupae, and cases of Phylloicus amazonas Prather 2003, P. fenestratus Flint 1974, and P. passulatus Prather 2003 are described and illustrated, and the adult females of P. amazonas and P. passulatus are illustrated. Additionally, the lateral coremata with an eversible membranous sac and the everted phallus of the male of P. passulatus are illustrated and described. Larval bionomics are presented for each species. First records of species are presented for Brazil (P. passulatus), Pará state (P. amazonas, P. dumasi Santos & Nessimian 2010, P. elektoros Prather 2003), and Tocantins state (P. fenestratus).